28.3k views
0 votes
Chris was asked to factor out the GCF from the following polynomial. Describe in 1 - 2 sentences the mistake that he made. -4k^7 - 8k^5 + 4k^44k^4 4k^4 4k^4GCF = 4k^4Answer = 4k^4 ( - k^11 - 2k^9 + k^8 )

1 Answer

3 votes

Solution:

Given the polynomial


-4k^7-8k^5+4k^4

To factor out the GCF, we have


4k^4(-k^3-2k+1)

Thus,


GCF:\text{ 4k}^4

Description:

Chris made mistakes in his division.


\begin{gathered} (-4k^7)/(4k^4)=-k^3 \\ (-4k^5)/(4k^4)=-2k \\ (4k^4)/(4k^4)=1 \end{gathered}

User Gabriel Tomitsuka
by
4.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.